Romatoid Arthritis Like Hand Deformities Associated with the Parkinson’s Disease: A Case Report - Bengi Öz; Serpil Bal; Asuman Memiş; Alev Gürgan (Archives of Rheumatology, 2007)
We present a case diagnosed as Parkinson’s disease that had hand deformities resembling the deformities of romatoid arthritis. Hand deformities can develop secondary to Parkinson disease and they might be similar to deformities of Romatoid arthritis. It was reported that swan neck deformity, ulnar deviation and hiperextension of metacarpophalangeal joints were associated with Parkinson’s disease. As these deformities can be observed in romatoid arthritis, careful differential diagnosis is mandatory. (Rheumatism 2007; 22: 117-9)